Modes and Twinning Stresses of Martensite Variants Rearrangements in Near-Stoichiometric Ni₂MnGa Single Crystal - Soolshenko, V.; Beloshapka, V. (Металлофизика и новейшие технологии, 2017)
The sequences of the thermally induced martensitic and intermartensitic L2₁ → 10M → 14M → L1₀ and L1₀ → 14M → 10M → L2₁ transformations are observed in Ni₅₀.₆Mn₂₈. ₅Ga₂₀.₉ single crystal on the cooling and heating branches of a thermal cycle. The modes of stress-induced intervariant transitions in the 10M, 14M, and L10 martensites are investigated on the basis of matrix approach, and the stresses of orientation-variants’ rearrangements are determined as a function of martensite structure, transition mode, and temperature. The twinning stress decreases along the L1₀, 14M, and 10M martensites with a decrease of period of a nanotwinned structure. Послідовності термічно індукованих мартенситних i міжмартенситних перетворень L2₁ → 10M → 14M → L10 i L10 → 14M → 10M → L2₁ спостерігаються у Ni₅₀.₆Mn₂₈. ₅Ga₂₀.₉ -монокристалі у термічному циклі охолодження та нагрівання. Досліджено види індукованих напругою міжваріантних переходів у 10M-, 14M- i L1₀ -мартенситах на основі матричного опису та визначено напруги перерозподілу орієнтаційних варіянтів, залежно від структури мартенситу, виду переходу та температури. Напруга двійникування зменшується уздовж L1₀ -, 14M-, 10M-мартенситів із зменшенням періоду нанодвійникованої структури. Последовательности термически индуцированных мартенситных и межмартенситных превращений L2₁ → 10M → 14M → L10 и L10 → 14M → 10M → L2₁ наблюдаются в Ni₅₀.₆Mn₂₈. ₅Ga₂₀.₉-монокристалле в термическом цикле охлаждения и нагрева. Исследованы виды индуцированных напряжением межвариантных переходов в 10M-, 14M- и L1₀ -мартенситах на основе матричного описания и определены напряжения перераспределения ориентационных вариантов в зависимости от структуры мартенсита, вида перехода и температуры. Напряжение двойникования уменьшается вдоль L1₀ -, 14M-, 10M-мартенситов с уменьшением периода нанодвойникованной структуры.